If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(3r+6)=6=6
We move all terms to the left:
-6(3r+6)-(6)=0
We multiply parentheses
-18r-36-6=0
We add all the numbers together, and all the variables
-18r-42=0
We move all terms containing r to the left, all other terms to the right
-18r=42
r=42/-18
r=-2+1/3
| 8x+5x+6=-35.6 | | 3(v+3)-4=5 | | H=4+33t+-16t2 | | 4-(1-7x)^1/3=0 | | 3(-2x+4)=6(-x+2) | | -5t+2t+9=18 | | 78898t=78 | | -4(2x-6)=-8 | | 319=11x+1 | | 6(-5x+x)=108 | | 2f+3=11f-22 | | 2f+3=11f-23 | | 2f+5=11f-24 | | -59=-4x | | 2((x-3)=3x-4 | | -2v−3v=-10 | | -8(7-6x)=-8 | | 32-2n=4n | | -4=-16/g | | 6a+2a=21 | | 30x-75=0 | | 2x-3+3x+3x-3+2x-4=360 | | -59=4x | | -4=-16g | | -3(m+10)=-15 | | 4d-13=2d+7 | | 1.2=2,4-3b | | 4d-12=2d+7 | | 1/4(12x+16)=1/3(15x-12) | | (-6-5k)=11 | | 4d-11=3d+7 | | 4d-11=1d+7 |